"The Little Mermaid” Dalam 2 Sajian Teks Yang Berbeda: Struktur Naratif A.J. Greimas - Ayu Putri Bhakti; Adi Setijowati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
ABSTRACTThis study aims to explore how the main character who hopes that he can turn into a complete human is told in the form of short stories and films. This study focuses on 2 texts with a female main character who is a beautiful mermaid, namely The Little Mermaid by Hans Christian Andersen (1837) and Walt Disney (1989). The two main female characters in the story are explained through the actential theory of A.J. Greimas. The focus of this research is the similarity of subjects but has different objects in the form of happiness defined by the main character. The findings of this study include: 1) The object in Hans Christian Andersen’s The Little Mermaid story is eternal life, while The Little Mermaid in Walt Disney version is married with a prince; 2) The opponent of both stories which is kind of happiness defined by the main character.Keywords: Fairy Tales, Happiness, True Love